ANALISIS KUALITAS LAYANAN DI KLINIK BIDANG KEDOKTERAN DAN KESEHATAN POLRES MAGELANG - Dewantoro, Fakhrul; Priyastiwi, Priyastiwi (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
The aim of this research is to analyze the quality of service at the Magelang Police BIDDOKES Clinic and to formulate the efforts made to improve the quality of service at the Magelang Police BIDDOKES Clinic.The results of the study stated that the quality of service at the Magelang Police BIDDOKES Clinic received patient responses with an average of saying they were satisfied with an average score of 3.90 and patient expectations regarding the quality of service at the Magelang Police BIDDOKES Clinic received patient responses with an average of saying it was very important. Average value 4.64. Then the gap that occurs between patient perceptions and expectations regarding the quality of service at the Magelang Police BIDDOKES Clinic shows that everything is a negative gap. The occurrence of a gap or negative discrepancy shows that the quality of service is small compared to community expectations. Efforts made to improve the quality of service at the Magelang Police BIDDOKES Clinic, based on the Cartesian Diagram are: (a) The main priority is treatment and examination services for patients, conformity of expected services with those informed, responsiveness of officers in providing services, ease of the referral process , the physical building of the clinic, and the appearance of the staff (clean, neat); (b) Maintained is the response of officers in handling patient complaints, providing health information to patients, the clinic providing fair service to all patients, the completeness of the medical equipment used, the condition of the medical equipment used and the condition of the service room (clean and comfortable); (c) Low Priority is correct administration and payment procedures, service in the clinical pharmacy installation, the attitude of staff listening to patient complaints, sympathy for patients and communication between staff and patients. (d) Excessive are the standards of service for referred patients, the politeness of health workers to patients, the ability of staff to provide services, guarantees and trust in services and medical staff having patient medical records.